Effects of environmental factors, age and genotype on sperm production and semen quality in Bos indicus and Bos taurus AI bulls in Brazil - Brito, LFC; Silva, AEDF; Rodrigues, L. H.; Vieira, F. V.; Deragon, LAG; Kastelic, J. P. (Elsevier B.V., 2002)
The effects of ambient temperature and humidity, month, age and genotype on sperm production and semen quality in AI bulls in Brazil were evaluated. Data from two consecutive years were analyzed separately. Seven Bos indicus and 11 Bos taurus bulls from one artificial insemination (AI) center were evaluated in Year 1 and 24 B. indicus and 16 B. taurus bulls from three AI centers were evaluated in Year 2. Ambient temperature and humidity did not significantly affect sperm production and semen quality, probably because there was little variation in these variables. Month accounted for less than 2% of the variation in sperm production and semen quality. Increased bull age was associated with decreased sperm motility (P < 0.10) and increased minor sperm defects (P < 0.001) in Year 1. B. indicus bulls had greater (P < 0.005) sperm concentration than B. taurus bulls in both years (1.7 x 10(9)/ml versus 1.2 x 10(9)/ml in Year 1 and 1.6 x 10(9)/ml versus 1.2 x 10(9)/ml in Year 2, respectively). Ejaculate volume was not significantly affected by genotype in Year 1 (6.6 ml versus 6.9 ml in B. indicus and B. taurus bulls, respectively), but B. indicus bulls had greater (P < 0.05) total (11.4 x 10(9) versus 8.2 x 10(9)) and viable (6.7 x 10(9) versus 4.9 x 10(9)) numbers of spermatozoa in the ejaculate than B. taurus bulls. In Year 2, B. taurus bulls had greater (P < 0.05) ejaculate volume than B. indicus bulls (8.2 ml versus 6.7 ml, respectively) and total and viable number of spermatozoa in the ejaculate were not significantly different between genotypes (10.3 x 10(9) versus 9.1 x 10(9) and 6.1 x 10(9) versus 5.4 x 10(9) in B. indicus and B. taurus bulls, respectively). Sperm motility was not significantly affected by genotype (mean, 59%). In Year 1, B. indicus bulls tended (P < 0.10) to have more major sperm defects and had more (P < 0.05) total sperm defects than B. taurus bulls (11.8% versus 8.7% and 13.6% versus 10.0%, respectively). In Year 2, B. indicus bulls tended (P < 0.10) to have more total sperm defects than B. taurus bulls (16.2% versus 13.3%, respectively). In conclusion, neither ambient temperature and humidity nor month (season) significantly affected sperm production and semen quality. B. indicus bulls had significantly greater sperm concentration and B. taurus bulls had significantly fewer morphologically defective spermatozoa. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: bull; semen; sperm; artificial insemination; season; tropics